A Comparative Analysis of Microbial Load and Diversity in Fresh and Smoked Catfish (Clarias gariepinus) from Selected Markets in Delta State, Nigeria - Odozie Esther Uche; Otoikhian C.S.O; Bosah B.O; Elkanah D.S (Darul Yasin Al Sys, 2026)
This study evaluated the microbiological quality and safety of fresh and smoked catfish (Clarias gariepinus) obtained from five markets (Amai, Umutu, Abbey, Obiaruku, Kwale) in Delta State, Nigeria, during both rainy and dry seasons. A total of 50 samples were analyzed for total aerobic plate count, coliform count, and specific microbial isolates using standard microbiological and biochemical methods, and the results were benchmarked against Standards Organization of Nigeria (SON) guidelines. The findings showed that the microbial quality of fresh fish was variable, with gill samples from Amai and Obiaruku in the rainy season exhibiting marginal levels of contamination (10³ CFU/g), whereas all smoked fish samples, irrespective of market or season, had satisfactory and significantly lower microbial loads (10¹–10² CFU/g), confirming the effectiveness of smoking as a preservation technique. Bacteriological analysis of fresh fish identified potential pathogens, including Staphylococcus aureus, Escherichia coli, Salmonella sp., and Klebsiella sp., while mycological assessment revealed the presence of Aspergillus fumigatus, Aspergillus niger, Mucor, and Fusarium species. The study concludes that, although smoking markedly improves the microbiological safety of catfish, the initially high contamination levels in fresh fish, especially the occurrence of pathogenic bacteria and potentially mycotoxigenic fungi—pose a significant public health risk and indicate critical points of post-harvest contamination within the supply chain that require targeted control measures.